Mechanical property and reliability of bimodal nano-silver paste with Ag-coated SiC particles. Issue 4 (2nd September 2019) - Zhang, Qiaoran; Zehri, Abdelhafid; Liu, Jiawen; Ke, Wei; Huang, Shirong; Latorre, Martí Gutierrez; Wang, Nan; Lu, Xiuzhen; Zhou, Cheng; Xia, Weijuan; Wu, Yanpei; Ye, Lilei; et al.
Abstract : Purpose: This study aims to develop a bimodal nano-silver paste with improved mechanical property and reliability. Silicon carbide (SiC) particles coated with Ag were introduced in nano-silver paste to improve bonding strength between SiC and Ag particles and enhance high-temperature stability of bimodal nano-silver paste. The effect of sintering parameters such as sintering temperature, sintering time and the proportion of SiC particles on mechanical property and reliability of sintered bimodal nano-silver structure were investigated. Design/methodology/approach: Sandwich structures consist of dummy chips and copper substrates with nickel and silver coating bonded by nano-silver paste were designed for shear testing. Shear strength testing was conducted to study the influence of SiC particles proportions on the mechanical property of sintered nano-silver joints. The reliability of the bimodal nano-silver paste was evaluated experimentally by means of shear test for samples subjected to thermal aging test at 150°C and humidity and temperature testing at 85°C and 85 per cent RH, respectively. Findings: Shear strength was enhanced obviously with the increase of sintering temperature and sintering time. The maximum shear strength was achieved for nano-silver paste sintered at 260°C for 10 min. There was a negative correlation between the proportion of SiC particles and shear strength. After thermal aging testing and humidity and temperature testing for 240 h, the shear strength decreased a little. High-temperature stability and high-hydrothermal stability were improved by the addition of SiC particles. Originality/value: Submicron-scale SiC particles coated with Ag were used as alternative materials to replace part of nano-silver particles to prepare bimodal nano-silver paste due to its high thermal conductivity and excellent mechanical property.